اثر تطبيق تقنيات الذكاء الاصطناعي وراس مال الفكري وانعكاساته على قيمة المشروع دراسة تطبيقية على فروع مصرف الجمهورية / المنطقة الغربية الزاوية (Comprehensive Journal of Science, 2026)
The study aims to examine the impact of applying artificial intelligence techniques and intellectual capital, and their effect on both the market and book value of projects, through the dimensions of the mediating variable (human capital, organizational structure, and external relations). To achieve the study’s objectives, the researchers adopted a descriptive-analytical approach. The study population consisted of all employees of the 15 branches of Al-Jumhouria Bank in the western region. The study sample included branch managers, department heads, section heads, internal auditors, and accountants from the aforementioned branches. A total of 56 questionnaires were distributed to a random sample, of which 51 valid responses were returned, representing a response rate of 91.07%.The researchers also reached a set of findings, providing empirical evidence supporting the acceptance of the study’s hypotheses. The study highlighted several key results, most notably:1ــ The relationship between artificial intelligence techniques and intellectual capital makes a statistically significant contribution to enhancing project value. 2  There is a statistically significant effect of using artificial intelligence techniques on intellectual capital, as follows .A . There is a statistically significant effect of using artificial intelligence techniques on human capital.B . There is a statistically significant effect of using artificial intelligence techniques on structural capital.c. There is a statistically significant effect of using artificial intelligence techniques on relational capital .3 . There is a statistically significant effect of intellectual capital on project value ."The study recommends expanding the application of artificial intelligence techniques due to their positive impact on project value, as well as the need to establish a general framework for their implementation in order to maximize the benefits. Furthermore, the study recommends incorporating artificial intelligence applications into the educational process within relevant institutions to provide the necessary knowledge for their application in economic projects.